Peristiwa Kriminalitas dalam Produksi Sastra Peranakan Tionghoa Masa Kolonial Tahun 1924 dan 1929 - Etsha Ari Kusuma Dianti (Madah: Jurnal Bahasa dan Sastra, 2025)
The social concept constructed by Alan Swingewood includes literature as a reflection of society, historical relationship between social phenomena and substance of literary works, and indicator of authorship productivity. Mostly the Peranakan Chinese people’s crime themed novels published in 1924 and 1929 contain social elements formed between the position of Chinese characters in the midst of the native figures. This research is descriptive-qualitative in order to collect data and present the results of the analysis based on narrative content. The results of this study show that the literary works of the Peranakan Chinese people’s criminal narratives were written based on the real situation at that time. Meanwhile, the trigger for the productivity of criminal narratives by Peranakan Chinese writers is due to the high interest of readers to Peranakan Chinese magazines. The contribution of this research is to harmonize the narrative with the real history of the era while presenting the expertise of Chinese peranakan writers in the past.